The anharmonic quartic force field infrared spectra of hydrogenated and methylated PAHs. Issue 2 (15th December 2017) - Mackie, Cameron J.; Candian, Alessandra; Huang, Xinchuan; Maltseva, Elena; Petrignani, Annemieke; Oomens, Jos; Buma, Wybren Jan; Lee, Timothy J.; Tielens, Alexander G. G. M.
Abstract : Reproducing and explaining the complex infrared spectra of functionalized polycyclic aromatic hydrocarbons through proper treatment of Fermi resonances. Abstract : Polycyclic aromatic hydrocarbons (PAHs) have been shown to be ubiquitous in a large variety of distinct astrophysical environments and are therefore of great interest to astronomers. The majority of these findings are based on theoretically predicted spectra, which make use of scaled DFT harmonic frequencies for band positions and the double harmonic approximation for intensities. However, these approximations have been shown to fail at predicting high-resolution gas-phase infrared spectra accurately, especially in the CH-stretching region (2950–3150 cm −1, 3 μm). This is particularly worrying for the subset of hydrogenated or methylated PAHs to which astronomers attribute the observed non-aromatic features that appear in the CH-stretching region of spectral observations of the interstellar medium (ISM). In our previous work, we presented the anharmonic theoretical spectra of three linear PAHs and five non-linear PAHs, demonstrating the importance of including anharmonicities into theoretical calculations. In this work we extend these techniques to two methylated PAHs (9-methylanthracene, and 9, 10-dimethylanthracene) and four hydrogenated PAHs (9, 10-dihydroanthracene, 9, 10-dihydrophenanthrene, 1, 2, 3, 4-tetrahydronaphthalene, and 1, 2, 3, 6, 7, 8-hexahydropyrene) in order to better understand the aliphatic IR features of substituted PAHs. The theoretical spectra are compared with the spectra obtained under matrix isolation low-temperature conditions for the full vibrational fundamental range and under high-resolution, low-temperature gas-phase conditions for the CH-stretching region. Excellent agreement is observed between the theoretical and high-resolution experimental spectra with a deviation of 0.00% ± 0.17%, and changes to the spectra of PAHs upon methylation and hydrogenated are tracked accurately and explained.